An Immunoregulatory Role of Interleukin-3 in Allergic Asthma - Krammer, Susanne; Yang, Zuqin; Zimmermann, Theodor; Xepapadaki, Paraskevi; Geppert, Carol I.; Papadopoulos, Nikolaos G.; Finotto, Susetta (Frontiers in Immunology, 2022)
BACKGROUND: Allergic asthma is a chronic airway inflammatory disease associated with airway mucus hyper-production. ILC2 cells, which express the Th2 transcription factor GATA3, have been associated with allergic asthma. The cytokine IL-3 is known to support eosinophil, basophil and mucosal mast cells differentiation and survival, however, its role on T regulatory cells as well as on lung ILC2 in pediatric asthma needs further investigation. OBJECTIVES: To investigate the role of IL-3 in preschool children and to explore its therapeutic role in experimental asthma. METHODS: In a cohort of preschool children with and without asthma, we analyzed the secretion of IL-3 in nasal pharyngeal fluid and IL-3 receptor (R) alpha chain mRNA expression in PBMCs. In a murine model of allergic asthma, we analyzed the phenotype of wild type untreated and rIL-3 intranasally treated asthmatic mice. RESULTS: IL-3 was found down-regulated in the nasal-pharyngeal fluid of children with partially controlled asthma, as compared to control children. Moreover, IL-3 was found induced in PHA stimulated PBMCs from children with asthma and treated with steroids. Finally, IL-3 in NFP directly correlated with the anti-inflammatory molecule sST2 in steroid treated asthmatic children. Intranasal rIL-3 delivery in vivo during the challenge phase, decreased the airway mucus production and inflammatory eosinophils. Moreover, rIL-3 given during the challenge phase reduced lung ST2 intGATA3+ ILC2, accompanied by an induction of T regulatory cells in the airways. CONCLUSIONS: IL-3 was found associated with steroid-resolved asthma. Moreover, treatment with rIL-3 resulted in amelioration of airway eosinophilia and mucus production, two main pathophysiological conditions associated with asthma in a murine model of allergic asthma. Thus rIL-3 opens new strategies for immunotherapy of this disease.